Opening Address - Mapp, Wayne (New Zealand Science Review, 2011)
I have been asked to talk about the Government’s vision for science and innovation over the next 20 years.Our vision is a simple one. It is that science and innovation is at the heart of our economy. They will be the means by which we grow and develop the economic and social future of New Zealand.